Comparison of defence and performance traits between one widespread clone and native populations in a major invasive plant species. Issue 3 (9th January 2018) - Rouifed, Soraya; Puijalon, Sara; Bardon, Clément; Meiffren, Guillaume; Buonomo, Antoine; Sebei, Nadia; Poussineau, Sophie; Vallier, Félix; Shimoda, Michiko; Piola, Florence
Abstract: Aim: The success of invasive species in their introduced range is often assumed to result from evolutionary changes in defence and growth traits, or as a response to more favourable conditions. The latter is assumed particularly for species exhibiting low, or even no, sexual reproduction in the introduced range. Location and Methods: Here, we compared Japanese (native range) and French (introduced range) populations of Fallopia japonica under common growth conditions in a glasshouse. We measured height, aboveground and belowground mass, stem stiffness, leaf toughness and secondary metabolites found in hydroalcoholic extracts of rhizomes of F. japonica, as well as the competitive response of Rubus caesius (a co‐occurring native species in the invaded range) in the presence of F. japonica from both ranges. Results: Aboveground biomass, height, stem stiffness and composition of secondary metabolites were not significantly different between the two ranges, showing that increased aboveground vigour observed in situ in France is probably the result of a plastic response following the release of abiotic or biotic constraints from the native range. On the other hand, belowground mass, effect on R. caesius, and leaf toughness were all higher in French populations, suggesting increases in competitive ability and defence mechanisms. These differences between France and Japan may be explained either by post‐introduction evolution or by the introduction in Europe, in nineteenth century, of an exceptionally vigorous clone (pre‐adaptation). Main conclusions: Our results provide evidence that the high vigour of this major invasive species in its introduced range is probably due to both a response to more favourable conditions and rapid evolution.